Commentary on Turing instabilities and symbolic material culture by Froese, Woodward and Ikegami. (February 2014) - Hodgson, Derek
Turing instabilities are invoked by Froese, Woodward, and Ikegami in support of the neural dynamics of the primary visual cortex that give rise to subjectively experienced geometric patterns or form constants. Although the authors provide a convincing case for the relevance of such instabilities to understanding the provenance of form constants, their reliance on altered states of consciousness and shamanic practices of Lewis-Williams is less convincing as the latter's proposal continues to be controversial. In this commentary, I will show that abnormal subjective states are neither necessary nor essential to understanding the universality of geometric art. In effect, the geometric art from the Middle Stone/Palaeolithic Age and later can be sufficiently explained by recourse to the normal function of the visual cortex in the context of the regular engagement with everyday materials.